Development of novel particle detector with multi pixel photon counter readout - Izyan Hazwani Hashim, 1986-; Yoshitaka Kuno, supervisor; Fakulti Sains (2010)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2010